(3JMSjf aGYdjI GdGOGA GdeDSSj ef NdGd JcfhdhLjG GdeYdheGJ (B/s - (3GdcSGSHI, hUaj YHO GdcQjes ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3eaghe JcfhdhLjG GdeYdheGJ h GdYdGbI HjfgG hHjf fXe GdeYdheGJ , GdGSJKeGQ aj JcfhdhLjG GdeYdheGJ h GdYhGed GdJj COJ Gdi GdGSJKeGQ aj (BIT (3GSJNOGeGJ JcfhdhLjG GdeYdheGJ h GdHfjJ GdJMJjI dgG , eOGNd bjGS GdaGYdjI aj GdGOGA GdeDSSj h GdJWQb Gdi cd ef fehPL GdGgOGa , GdMUhd Ydi GdehGQO , GdYedjGJ GdOGNdjI , CUMGH GdeUGdM h fehPL Gdbje GdeJfGaSI , HWGbI GdJSLjd GdeJhGRfI , GdJYQja HeDSSI GdefGWb GdMQI h CfhGYgG h fTCI GdefGWb GdMQI aj GdGQOf , CgOGagG h GdGYaGAGJ h GdJSgjdGJ GdJj JhaQgG (B.s
(3eQGLY U(B.223 (3;LOGhd U(B.337 (3; GTcGd U(B.340s
Keywords: (3GdeDSSGJs; (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s